(untitled) (Ibrahim Medical College Journal, 2009)
Enteric fever commonly causes fatality from abdominal complications or toxemia but it can also cause death from complications of myocarditis albeit rarely. In September, 2005 a 22 year old man was admitted in BIRDEM with the features of pneumonia. Later on, the patient developed acute left ventricular failure and ultimately diagnosed as a case of drug resistant enteric fever with myocarditis Ibrahim Med. Coll. J. 2007; 1(1): 34-37 Key words: Enteric fever; abdominal complications doi: 10.3329/imcj.v1i1.2893